How diverse were ferns in the Baltic amber forest?. Issue 4 (9th August 2019) - Sadowski, Eva‐Maria; Seyfullah, Leyla J.; Regalado, Ledis; Skadell, Laura E.; Gehler, Alexander; Gröhn, Carsten; Hoffeins, Christel; Hoffeins, Hans Werner; Neumann, Christian; Schneider, Harald; Schmidt, Alexander R.
Abstract: Diverse temperate forest types and a high atmospheric humidity have recently been suggested for the Eocene source area of Baltic amber. However, ferns are astonishingly rare as inclusions in this amber, which is in contrast to other seed‐free land plants, fungi, and lichens. Moreover, the identities of some of the few described putative fern taxa are dubious, and some fossils were even assigned to the Paleozoic seed fern genera Alethopteris, Pecopteris and to the form genus Sphenopteris containing Paleozoic and Mesozoic fern‐like leaf fossils. Here, we review previously described fern inclusions from Baltic amber and identify further fern‐like leaf inclusions as belonging to the extant angiosperm genus Comptonia (sweet ferns, Myricaceae). We conclude that only one taxon, Matonia striata (Matoniaceae), can with confidence be identified as a Polypodiopsida representative. Although " Pecopteris " humboldtiana is so far only known as sterile foliage, its leaf morphology strongly suggests that also this taxon belongs to the Polypodiopsida rather than to any other tracheophyte lineage. We propose accommodating " Pecopteris " humboldtiana in the new genus Berendtiopteris . " Alethopteris " serrata and " Sphenopteris" phyllocladoides are not to be regarded as evidence of ferns from Baltic amber. Reinvestigation of the holotypes of these two taxa did not reveal to which tracheophyte lineages these fossils belong. We suggest that the scarcity of fern remains from Baltic amber may reflect both a relatively low fern diversity in the source area of the fossil resin, and an absence or rarity of epiphytic and climbing ferns as observed in modern temperate forest ecosystems.